Synthesis and Characterization of 1-(1-Methyl-4-N-cyanoethyl-N-benzene sulphonyl amino benzylidine) 4-Aryl thiosemicarbazone - Gandhi, Sandhya; Pradhan, Alka; Dave Gautam, Mangla (Asian Journal of Chemistry, 2016)
The synthesis of 1-(1-methyl-4-N-cyanoethyl-N-benezene sulphonyl amino benzylidine) 4-aryl thiosemicarbazones were carried out by refluxing 4-aryl thiosemicarbazide and 1-methyl-4-N-cyanoethyl-N-benzenesulphonyl benzaldehyde in stoichiometric amounts dissolved in aqueous ethanol in presence of few drops of acetic acid.